European traded gas hubs: Their continued relevance - Patrick Heather (The Oxford Institute for Energy Studies, 2023)
This Paper gives the results of the Author's in-depth analysis of the European traded gas hubs in 2020, as well as explaining the 'LNG effect' on increased volumes in Belgium, France, and Spain in particular. The purpose of the analysis is to confirm that the hubs are all still relevant despite the recent upheaval in the energy markets, and that the TTF price in particular is still representative of the gas flowing in the grid. The European gas markets have experienced a very turbulent ride over the past three years which has resulted in a severe readjustment of the European traded gas markets. There have been ongoing political and energy industry debates regarding not just the future of natural gas in the energy mix, but also how to resolve the immediate problem of 'replacing' Russian gas for Europe's demand needs now and for the next few years? Politically, there have been a number of interventions suggesting that the traded gas markets and the Dutch Title Transfer Facility (TTF) hub in particular, are no longer representative of the price of natural gas in the grid. The purpose of this Paper is to analyse the results of the trading data in 2022 for the European traded gas hubs, in order to be able to assess whether these hubs continue to be relevant, or not, in the pricing of long term physical gas contracts? It will look at the TTF in particular, as this hub has for several years now been the most liquid by far in Europe, and has been widely used as the reference price for physical wholesale gas contracts. From the analysis carried out in this paper, there is no doubt that several of the European hubs do provide the right pricing signals in their respective markets, and even provide the ability for market participants to risk manage some of their portfolio exposures. On a global level, the analysis shows that the TTF is truly the leading pricing benchmark for North-West Europe and indeed many other European countries also, as well as being used to price some LNG cargoes destined for Europe. It has become an investment asset class in its own right and there are signs that it has become a global benchmark too. The final conclusion of this paper is that all European traded gas hubs are most definitely still relevant, if only to enable the safe and efficient balancing of the gas grids; but they can also be much more than that. Some are relevant for actual local market pricing, whether wholesale or retail, and possibly for limited (mainly short term) risk management purposes. The Dutch TTF though is all those things, and is also used by a great many market participants, from all around the world, as a reliable price marker for several surrounding European countries, as well as on a wider scale across Europe, and even globally. Yes, the TTF in particular does continue to be relevant in the pricing of long term physical gas contracts and, yes, it is still representative of the price of gas in the Dutch, and wider European, grid network at any given time.
Keywords: 330; EU gas market correction mechanism; European (traded) gas hubs; Gas benchmarks; Gas hub are relevant; Gas hubs no longer representative; Gas price benchmarks; Global churn rates; Global gas benchmarks; TTF a reliable price marker; TTF is relevant; TTF is representative